2021
DOI: 10.3390/ijms222413674
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells (iPSCs) and Gene Therapy: A New Era for the Treatment of Neurological Diseases

Abstract: To date, gene therapy has employed viral vectors to deliver therapeutic genes. However, recent progress in molecular and cell biology has revolutionized the field of stem cells and gene therapy. A few years ago, clinical trials started using stem cell replacement therapy, and the induced pluripotent stem cells (iPSCs) technology combined with CRISPR-Cas9 gene editing has launched a new era in gene therapy for the treatment of neurological disorders. Here, we summarize the latest findings in this research field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 90 publications
(130 reference statements)
0
8
0
2
Order By: Relevance
“…Yamanaka et al, who first reported iPSCs derived from murine fibroblasts in 2006 [ 6 ], was awarded the Nobel Prize in Medicine only six years after the first description, in recognition of the potential of iPSCs for regenerative medicine and disease modeling. Reprogrammed stem cells are attracting attention not only in the production of next-generation immune-compatible stem cell therapeutics, but also as models for identifying disease etiology, therapeutic efficacy, and toxicity testing [ 28 ]. Recently, iPSCs have gained attention as precursor cells for organoid research [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yamanaka et al, who first reported iPSCs derived from murine fibroblasts in 2006 [ 6 ], was awarded the Nobel Prize in Medicine only six years after the first description, in recognition of the potential of iPSCs for regenerative medicine and disease modeling. Reprogrammed stem cells are attracting attention not only in the production of next-generation immune-compatible stem cell therapeutics, but also as models for identifying disease etiology, therapeutic efficacy, and toxicity testing [ 28 ]. Recently, iPSCs have gained attention as precursor cells for organoid research [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reprogramming process may introduce genetic and epigenetic abnormalities that could affect the safety and efficacy of iPSC-based therapies. For instance, the use of viral vectors for reprogramming may result in insertional mutagenesis, which can disrupt normal gene function and increase the risk of tumorigenicity [ 101 ].…”
Section: The Potential Of Different Stem Cell Typesmentioning
confidence: 99%
“…In this context, CRISPR-Cas9 technology has opened the possibility of directly editing genomic sequences, elucidating the contribution of genetics to disease, by promoting the creation of more accurate cellular and animal models. Combination of iPSC technology with CRISPR-Cas9 gene editing has launched a new era in gene therapy for the treatment of neurological disorders [ 78 , 79 ].…”
Section: Perspectivementioning
confidence: 99%